Effects of postpartum hormonal changes on the immune system and their role in recovery - Xueqin Wu; Rong Jin (Acta Biochimica Polonica)
BackgroundThe postpartum period involves complex physiological changes, notably in hormone levels, that significantly influence immune system function. Hormonal regulation during pregnancy prevents maternal immune rejection of the fetus, but following childbirth, these hormone levels drop rapidly, leading to immune reconstitution.AimThis review investigates the impact of hormonal changes on immune system dynamics during the postpartum period and highlights their implications for maternal recovery.MethodsThe study analyzed current literature, focusing on hormonal influences, particularly cortisol, prolactin, estrogen, and progesterone, on immune reconstitution with associated inflammatory responses in the postpartum period.ResultsPostpartum immune reactivation, triggered by hormonal shifts, can lead to a resurgence of inflammatory reactions. This process, characterized by increased cortisol and prolactin levels and a rapid decline in estrogen and progesterone, could exacerbate dormant autoimmune conditions or trigger latent infections, making this period especially vulnerable to immune-related complications.ConclusionHormonal and immune responses are closely interdependent in the postpartum period, leading to heightened susceptibility to infections, autoimmune flare-ups, and other immune-related disorders. For improved postpartum care and enhanced maternal health outcomes, more research is necessary to clarify the mechanism of immune reconstitution, find possible hormonal indicators, and create focused therapeutic approaches. This review further highlights the critical role of hormonal-immune crosstalk in postpartum mood disorders (PPD, postpartum anxiety [PPA], and postpartum psychosis [PP]), proposing integrated biomarkers for early intervention.